Islamic Religious Education Teacher's Strategy in Forming Students' Religious Character - Wirandhika, Ashila Elvaretta; Hermanto, Hermanto (AT-TA'LIM, 2023)
Character education values such as discipline, honesty and responsibility need strengthening in their implementation at this time. We can see this in how the youth behave. For example, many students violate school rules, do not do their assignments, cheat, or even skip classes for no reason. These things can apparently arise due to the loss of religious character in students. The aim of this study is to describe the strategies used by Islamic Religious Education teachers in shaping the religious character of students and their supporting and inhibiting factors. This method of research is qualitative research. This research uses a field research approach, namely from the process, if the activities at SMPN 3 pages in the Islamic Religious Education strategy program in Shaping Students' Religious Character. Researchers used purposive sampling techniques to select informants, and to collect data, researchers used observation, interviews, and documentation. For the data validity, researchers use triangulation and data analysis, which is then processed and arranged systematically so that it can be interpreted and produce something in the form of thoughts, theories, opinions, or even new ideas. The results showed that this strategy has not been fully successful because there are many obstacles. Almost everything is limited and not all programs can run efficiently.